Anti-inflammatory effect and mechanism of stytontriterpene D on RAW264.7 cells and zebrafish - Yu, Chuqin; Qiu, Gao; Liu, Xiangying; Xie, Quanwei; Lin, Zonghao; Wang, Feng; Cai, Lei (Frontiers in Pharmacology, 2025)
IntroductionStytontriterpene D ( STD ) is a compound isolated from dried resin of Styrax tonkinensis (Pierre) Craib ex Hartw. In this study, we explored the anti-inflammatory effect of STD in vitro and in vivo and examined its potential anti-inflammatory mechanism for the first time.MethodsIn vitro, we evaluated the toxicity of STD to RAW 264.7 cells using the CCK8 method and detected the reactive oxygen species (ROS) and nitric oxide (NO) contents in cells using diacetyldichlorofluorescein (DCFH-DA) and the Griess method. We detected the levels of interleukin-6 (IL-6), interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), inducible nitric oxide synthase (iNOS), interleukin-10 (IL-10), and arginase-1 (ARG1) via enzyme-linked immunosorbent assay and measured the expression of related proteins in the NF-κB pathway via western blotting. The toxicity of STD to AB zebrafish was detected in vivo, and the recruitment of neutrophils and macrophages was evaluated in tail cut-induced and copper sulfate-induced zebrafish inflammation models. We used quantitative real-time polymerase chain reaction to study the expression of inflammation-related genes in zebrafish with inflammation induced by copper sulfate.ResultsIn lipopolysaccharide (LPS)-induced RAW 264.7 cells, STD decreased IL-6, IL-1β, NO, ROS, and TNF-α production, and increased the expression of IL-10 and ARG1 while also blocking inhibitory κBα (IκBα) phosphorylation and suppressing P65 nuclear translocation. STD also reduced the recruitment of inflammatory cells in zebrafish with inflammation induced by tail cutting and copper sulfate. STD not only reduced the copper sulfate–induced gene expression of zebrafish inflammatory factors, but it also inhibited the mRNA levels of NF-κB p65 and IκBα.ConclusionThese results demonstrated that STD has an obvious anti-inflammatory effect, and its intrinsic molecular mechanism is possibly caused by inhibiting the NF-κB signaling pathway and regulating the phenotypic changes of M1 and M2 macrophages. Thus, STD may play a potential role in the treatment of inflammatory diseases.